2018
DOI: 10.1038/s41467-018-07012-4
|View full text |Cite
|
Sign up to set email alerts
|

Competing protein-protein interactions regulate binding of Hsp27 to its client protein tau

Abstract: Small heat shock proteins (sHSPs) are a class of oligomeric molecular chaperones that limit protein aggregation. However, it is often not clear where sHSPs bind on their client proteins or how these protein-protein interactions (PPIs) are regulated. Here, we map the PPIs between human Hsp27 and the microtubule-associated protein tau (MAPT/tau). We find that Hsp27 selectively recognizes two aggregation-prone regions of tau, using the conserved β4-β8 cleft of its alpha-crystallin domain. The β4-β8 region is also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
111
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(124 citation statements)
references
References 49 publications
13
111
0
Order By: Relevance
“…Recently, Freilich et al. have studied the different interactions of a representative of this class, namely Hsp27, with the microtubule‐associated protein tau . Misfolding and aggregation of tau are at the basis of several neuropathies.…”
Section: Modulating Biological Functions By Targeting Protein–proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Freilich et al. have studied the different interactions of a representative of this class, namely Hsp27, with the microtubule‐associated protein tau . Misfolding and aggregation of tau are at the basis of several neuropathies.…”
Section: Modulating Biological Functions By Targeting Protein–proteinmentioning
confidence: 99%
“…Misfolding and aggregation of tau are at the basis of several neuropathies. Interestingly, Hsp27 was shown to interact with two different aggregation‐prone regions of tau through a conserved cleft, which incidentally also mediates self‐interaction (Hsp27–Hsp27) …”
Section: Modulating Biological Functions By Targeting Protein–proteinmentioning
confidence: 99%
“…Thus, were the IxI/V binding affinity to be lowered, subunit exchange would occur more slowly and the average oligomer size would increase (24,25). Previous studies independently support such a mechanism, as other HSP27 mutants in the IxI/V motif have been shown to increase the molecular mass, including the HSP27 variants P182S (40) and GPG (34), and other IxI/V mutations (32)(33)(34)(35). In addition, it has been demonstrated that other regions of sHSPs can also interact with the ACD, including NTD-β4/β8 groove interactions observed in a crystal structure of HSPB6 (69) and NTD-ACD dimer interface contacts as seen in a crystal structure of the HSPB2-HSPB3 hetero-tetramer (70).…”
Section: Discussionmentioning
confidence: 90%
“…Previous solution-state NMR studies of WT HSP27 only observed resonances from the disordered CTR, and thus could not probe CTR binding to the ACD in context of the fulllength protein (47,48). We therefore turned to the isolated ACD, which forms stable dimers (2 x 10 kDa) that are known to bind to a peptide encompassing the IxI/V motif of the CTR (20,22,31,33,34,37).…”
Section: P182l Forms Large Oligomers Both In Vitro and In Vivomentioning
confidence: 99%
See 1 more Smart Citation